Evaluating the Antimicrobial Activities and Phytochemical screening of the Leaf Extract of Mitracarpus scaber - M. Oghenejobo; K. E. Uvieghara; E. Omughele (Research Aspects in Biological Science Vol. 2, 2022)
The aim of this work is to evaluate the anti-microbial activities of the leaf extract of Mitracarpus scaber. The results demonstrate that at different doses, it inhibits Pseudomonas aeruginosa, Proteus vulgaris, Escherichia coli, Staphylococcus aureus, and Trychophyton mentagraphytes. Secondary metabolites such as steroids, reducing sugars, alkaloids, tannins, tepenoids, saponins, cardiac glycosides, and general glycosides were discovered during the phytochemical screening. This suggests that Mitracarpus scaber can be used as herbal mixture to treat skin diseases caused by bacteria and fungi.